Application of ARMA-GARCH Models on Solar Radiation for South Southern Region of Nigeria (Journal of Informatics and Mathematical Sciences, 2017)
Modeling solar radiation is a necessity for the utilization of the benefits it brings to mankind. Time series analysis has proved to stand out amidst other statistical tools when estimating and forecasting solar radiations and their variations. In this paper, a mixture of the Autoregressive Moving Average (ARMA) and Generalized Autoregressive Conditional Heteroscedasticity (GARCH) time series models were implemented on the solar radiation series for Port Harcourt meteorological station, located at the south-southern part of Nigeria, to capture and model the conditional mean and volatility that may exist in the series. After subjecting the models to some evaluation metrics for model adequacy, the results gave appropriate ARMA model for the station, indicated the presence of volatility in the radiation series and these volatilities were modeled using the combination of ARMA-GARCH models, which produced a better estimate than the ARMA models alone.
Keywords: Models; Solar radiation; ARMA; GARCH; Volatility